2011
DOI: 10.1038/emboj.2011.17
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and allosteric potential of the AMPA receptor N-terminal domain

Abstract: Glutamate‐gated ion channels (ionotropic glutamate receptors, iGluRs) sense the extracellular milieu via an extensive extracellular portion, comprised of two clamshell‐shaped segments. The distal, N‐terminal domain (NTD) has allosteric potential in NMDA‐type iGluRs, which has not been ascribed to the analogous domain in AMPA receptors (AMPARs). In this study, we present new structural data uncovering dynamic properties of the GluA2 and GluA3 AMPAR NTDs. GluA3 features a zipped‐open dimer interface with unconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
109
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(119 citation statements)
references
References 69 publications
(134 reference statements)
10
109
0
Order By: Relevance
“…Similarly, the second extracellular portion, the N-terminal domain (NTD), crystallized as a dimer, in both AMPA and kainate receptors (Fig. 11.1b) (Clayton et al 2009;Jin et al 2009;Kumar et al 2009;Karakas et al 2009;Kumar and Mayer 2010;Sukumaran et al 2011). This overall twofold symmetry of the extracellular portion is also observed at the level of the intact receptor, whereas the ion channel adopts fourfold symmetry ).…”
Section: Dimer Formationmentioning
confidence: 83%
“…Similarly, the second extracellular portion, the N-terminal domain (NTD), crystallized as a dimer, in both AMPA and kainate receptors (Fig. 11.1b) (Clayton et al 2009;Jin et al 2009;Kumar et al 2009;Karakas et al 2009;Kumar and Mayer 2010;Sukumaran et al 2011). This overall twofold symmetry of the extracellular portion is also observed at the level of the intact receptor, whereas the ion channel adopts fourfold symmetry ).…”
Section: Dimer Formationmentioning
confidence: 83%
“…This preference appears to be an intrinsic property of GluA1 and GluA2 sequences because changing SPs do not affect the linear I-V curves. Previous studies demonstrated that heterodimers could be formed both in isolated ATDs of GluA2 and GluA3 (39,40) and in kainate receptors (20,41). The velocity sedimentation study of isolated ATDs shows that the heterodimer of GluA1/A2 ATDs has the smallest dissociation constant (K d ); thus, the heterodimers are preferred (31).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, crystal structures of the Zn 2ϩ -bound and free NTD of the GluN2B subunit indicate that the NTD also favors a closed conformation in the absence of Zn differs from that in NMDA receptors, and a significant closure of the putative ligand-binding cleft in the AMPA receptor NTD is thought to be unlikely. AMPA receptor NTDs have, however, been shown to display flexibility (a prerequisite for an allosteric role), ranging from large-scale domain movements to more subtle conformational fluctuations (6,8,(53)(54)(55). A wide range of NTD conformations, some differing substantially from the arrangement in GluA2 cryst, have been reported on the basis of electron microscopic (16, 53, 56 -58) and atomic force microscopic (55) analyses of purified AMPA and kainate receptor preparations, supporting the view that the NTD can assume different conformations, at least under the specific experimental conditions used.…”
Section: Discussionmentioning
confidence: 99%